Pengaruh Metode Storytelling Terhadap Minat Belajar Siswa Kelas VII Pada Mata Pelajaran Tarikh di SMP-IT AL-Irsyad Al-Islamiyyah Karawang - Sutejo, Yusuf; Bariah, Oyoh; Makbul, M. (Peneliti.net, 2025)
Education plays a very important role in human life, the achievement of learning objectives depends on the interaction of students and teachers and the teacher's ability to choose appropriate learning methods. This creates a pleasant learning environment and encourages student interest to be active in the learning process. So this study aims to find the effect of the storytelling method on student interest in learning tarikh subjects. This research was conducted at SMPIT AL-Irsyad AL-Islamiyyah Karawang.The method used in this research is quantitative with ex post facto method. With a population of 92 students and samples taken 92 students with sampling using saturated samples. Data were collected through questionnaires and documentation. Then analyzed using descriptive analysis and inferential statistics. The research results obtained show: 1) An overview of the storytelling method for seventh grade students in the subject of tarikh at SMPIT AL-Irsyad AL-Islamiyyah Karawang. That 12 respondents (13.04%) were in the low category, 65 respondents (70.65%) were in the medium category, and 15 respondents (16.30%) were in the high category. From these data that the storytelling method for seventh grade students at SMPIT AL-Irsyad AL-Islamiyyah Karawang is in the medium category. 2) An overview of the learning interest of seventh grade students in the subject of tarikh at SMPIT AL-Irsyad AL-Islamiyyah Karawang. That 18 respondents (19.57%,) were in the low category, 55 respondents (59.78%) were in the medium category and 19 respondents (20.65%) were in the high category. From these data that interest in learning in seventh grade students at SMPIT AL-Irsyad AL-Islamiyyah Karawang is in the medium category with a percentage of 59.78%. 3) The storytelling method has an influence on the learning interest of students class VII in the subject of tarikh at SMPIT AL-Irsyad AL-Islamiyyah Karawang. This can be seen from the results of hypothesis testing with a level of 0.05 through SPSS version 25 obtained a result of 0.001 <0.05 so that H0 is rejected and Ha is accepted. Meanwhile, based on the R square value, the value is 12.5%. So it can be concluded that there is an influence between the use of the storytelling method on student interest in learning by 12.5% of class VII in the subject of tarikh at SMPIT AL-Irsyad AL-Islamiyyah Karawang.